Экономика и управление в нефтегазовой отрасли: учебно-методическое пособие - Болсуновская Л. М. Людмила Михайловна; Шендерова И. В. Инна Владимировна; Вершкова Е. М. Елена Михайловна; Малюкова Д. С. Дарья Сергеевна (Томск, Изд-во ТПУ, 2010)
Заглавие с титульного экрана